'I felt like a man': West Indian troops under fire during the First World War. (3rd July 2018) - Maguire, Anna
ABSTRACT: This article examines representations of the British West Indies Regiment's service during the First World War to explore how limits on their service were negotiated and how tropes of 'martial races' were adapted to ensure the contributions of West Indian men were recognised. The article examines West Indian experiences in Europe and the Middle East, drawing on a rich variety of textual and visual sources: official histories of West Indian regiments, memoirs written by padres who served with the troops, letters from the men as published in newspapers like the Daily Gleaner and the Jamaica Times, and official photographs. It argues that 'combat gnosticism' was replicated in another form within these representations to construct a definition of military service that included these black men and validated their contributions.